2009
DOI: 10.1080/09593330902778849
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of VOCs in biofilters inoculated with fungi and microbial consortium

Abstract: An experimental study on the removal of xylene vapours from an air stream was conducted on three identical upflow laboratory-scale wood-chips-based bed biofilters. Three different inoculums were used: fungi (Phanerochaete chrysosporium and Cladosporium sphaerospermum), a bacterial consortium (EVB110), and a mixed culture of fungi and EVB 110. The empty bed gas residence time was 59 s, and various inlet concentrations of the contaminant were tested. The results obtained revealed a strong correlation between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 22 publications
3
8
0
Order By: Relevance
“…The temperatures in the middle module increased up to 4 • C by days 13 and 14 after irrigation, while the temperature in the lower zone gradually increased from the first day and obviously decreased with the next irrigation. This close correlation between biofilter's performance and temperature was also observed by Jorio et al [29]. In accordance with this study, Son et al [30] showed that the ethylbenzene was not equally degraded over the depth of a biofilter packed with composting material after water irrigation.…”
Section: Influence Of Water Irrigation On Short-term Biofilter and Mosupporting
confidence: 91%
“…The temperatures in the middle module increased up to 4 • C by days 13 and 14 after irrigation, while the temperature in the lower zone gradually increased from the first day and obviously decreased with the next irrigation. This close correlation between biofilter's performance and temperature was also observed by Jorio et al [29]. In accordance with this study, Son et al [30] showed that the ethylbenzene was not equally degraded over the depth of a biofilter packed with composting material after water irrigation.…”
Section: Influence Of Water Irrigation On Short-term Biofilter and Mosupporting
confidence: 91%
“…. As previously described in the literature, two distinct regimes can be interpreted from this figure, i.e ., the diffusion limitation regime (DLR) and the reaction limitation regime (RLR) . In DLR, the diffusion of gaseous species through the biofilm is the rate controlling step in the biodegradation of VOCs.…”
Section: Resultsmentioning
confidence: 99%
“…Following the experience of earlier investigations carried out by other authors the present experimental studies lasted 1 year (Choi and Oh, 2002;Dorado et al, 2010;Gracy et al, 2006;Jorio et al, 2009;Trusek-Holownia et al, 2012;Vaiškūnaitė et al, 2005Vaiškūnaitė et al, , 2008Vaiškūnaitė et al, , 2011.…”
Section: Investigation Proceduresmentioning
confidence: 99%